New Methods for Predicting Strain Demand of Arctic Gas Pipelines across Permafrost under Frost Heave Displacement - Xinze Li; Qingbai Wu; Huijun Jin (Geofluids)
With increasing gas resource development in the Arctic region, gas pipeline installations in permafrost regions are becoming important. Frost heave of pipeline foundation soils may occur when a chilled gas pipeline passes through unfrozen areas with frost-susceptible soils. The stress and strain behaviors caused by the differential frost heave will directly affect the safety of the pipeline. A nonlinear finite element model (FEM) computing the mechanical responses of the buried gas pipeline subjected to frost heave load was established and successfully validated with the results of a large-scale indoor pipe-soil interaction experiment carried out in Caen in France. Utilizing C# language and object-oriented visual programming techniques, a new customized parametric strain calculation software was developed. The effects of pipe diameter, pipe wall thickness, pipe internal pressure, and peak soil resistance on the longitudinal strain of X60, X70, and X80 steel pipes have been investigated quantitatively. For the first time, a fitting semiempirical equation and trained backpropagation neural network (BPNN) for predicting pipeline strain demand subjected to frost heave load were proposed based on 2688 groups of FEM results. The comparison results have proved their high accuracy and lower running time cost. The proposed new methods can be applied in the strain-based pipeline design and safety evaluation of pipelines in service. It is in the hope of supplementing existing theory and identifying new approaches for arctic gas pipeline installations.